How Does Platelet-Rich Plasma Injection in Ovaries of Poor Responders Affect the Retrieved Oocytes, and Anti Mullerian Hormone: A Clinical Trial - Ensieh Shahrokh Tehraninejad; Maryam Olsadat Razavi; Azadeh Tarafdari Menshadi; Mamak Shariat; Saiedeh Shahsavari; Fedyeh Haghollahi; Elham Azimi Nekoo (Journal of Family and Reproductive Health, 2023)
Objective: Platelet Rich Plasma (PRP) is proposed to have important role in cell division and proliferation, angiogenesis and health. This study evaluates the effect of a single injection of autologous PRP on ovarian response markers in women with poor ovarian response (POR). Materials and methods: This non-randomized clinical trial was conducted between August 2020 and September 2021. Fifty six women with Bologna criteria for POR willingly chose to participate in one of the following groups: PRP for one cycle in the time of oocyte pickup (OPU) (intervention group, n= 34) or control group (n=22).The primary outcomes were: number and quality of oocytes in coming 2 cycles of ICSI, and Anti Mullerian Hormone (AMH) level two months after PRP injection. The secondary outcomes were the number and quality of embryos and chemical pregnancy rate after embryo transfer. Results: A total of 45 participants continued the study, of which 23 were in the intervention group and 22 in control group. There were no demographic differences between two groups. At a two cycle follow up, PRP group experienced a significant improvement in AMH level and there was no respective change in control group. In one year follow up the overall pregnancy rates were same in both groups (3% Vs. 0, p=.60), while there was no difference in cumulative number and quality of embryos. Conclusion: PRP injection can improve ovarian reserve marker without adverse effects. Further evidence is required to evaluate the impact of PRP on assisted reproduction outcomes.